FINLAND’S MARATHON IN NATO: CONSTRUCTION OF NEW MENTAL LANDSCAPE - Marina M. Yanglyaeva (Научно-аналитический вестник Института Европы РАН, 2024)
The article deals with the preparation measures delivered by Finnish government and NATO institutions specially designed for strategic propaganda to influence public opinion towards the North Atlantic Treaty Organisation. The author draws attention to the activities of the Finnish media to promote the anti-Russian narratives of the Alliance in the public sphere in Finland. The methods of political media geography and political mediametry were applied to obtain selective em- pirical material. The author analyses the processes of transformation of «Euro-neutral» and the cre- ation of the required mental landscape. The research explores the dynamics of two main mediamet- ric indicators – the number of publications and aggressiveness indexes for Finland and Sweden – and compares the obtained data with Internet statistics extracted from the Google system from 2010 to 2023, which is based on the Finnish Internet search «NATO-theme» and «Finland in NATO». Despite a large number of Finnish citizens, including politicians who is opposed to NATO member- ship, the Finnish media has changed public’s mode of thinking over the past decades. The image of NATO is strengthening in the mental landscape of Finland, which over time can become a stable morphosculpture. The author concludes that the transformation of Finnish citizens’ thought-pat- terns is used to instil separatist sentiments in the northwestern borders and discredit the govern- ment of Russia.